Optimization of enzymatic pretreatment and saccharification processes of sawdust for bioethanol production - Ahmed Hashabra, Amani Mohammad (2018)
A widespread interest has been devoted to the production of ethanol from sustainable renewable materials to compensate for the impending fossil fuel crisis. Lignocellulosic biomasses, such as sawdust and others, are an attractive, abundant, cheap and non-food competitive biomass feedstock for cheaper ethanol production. However, the recalcitrant structure of these materials necessitates a pretreatment process for a complete or partial breakdown of the lignin in the cell wall of these biomasses. Most of the pretreatment techniques require the use of chemicals and energy which poses a threat to the environment and the whole process as well. This study embarked on a statistical optimization of the pretreatment and saccharification processes of sawdust for bioethanol production in an environmentally-friendly manner. The study process involved the screening of the process parameters using One-Factor-At-a-Time (OFAT) to determine the optimum range and significance of each parameter in the was evaluated for bioethanol production using Saccharomyces cerevisiae as the fermentation organism. The bioethanol yield based on the total sugar content and biomass content was achieved as 29.4% (w/v) and 9.78% (w/v), respectively. These enzymatic pretreatment and saccharification processes can be considered as one of the renewable efforts towards reducing greenhouse gas emissions and environmental protection from global warming.